Yield and Economic Potential of Spring‐Planted, Pea–Barley Forage in Short‐Season Corn Double‐Crop Systems. (1st November 2017) - Raskin, Daniel; Wells, M. Scott; Grossman, Julie M.; Coulter, Jeffrey A.; Sheaffer, Craig C.
Abstract : Core Ideas: Biomass yield is similar between sole‐crop grain corn forage–silage corn double‐crop systems. Nitrogen fertilizer does not increase net economic return from forage–silage corn double‐crop systems. Double‐cro pea–barley forage–silage corn is not a profitable alternative to sole‐crop corn in the upper Midwest. Double cropping with forages can increase dry matter (DM) yield and N‐use efficiency over sole‐crop (SC) systems, but reductions in primary crop yield can limit economic return. This study assessed whether a double‐crop (DC) system coupling a legume–cereal biculture forage with early maturing corn can reduce fertilizer N input and compete economically with SC corn. Biomass yield, N uptake, residual soil NO3 –N, and economic net return were measured in two DC and one SC systems in four experiments conducted in Minnesota between 2014 and 2016. In DC systems, a field pea ( Pisum sativum L.)–barley ( Hordeum vulgare L.) forage biculture was double cropped with a dual‐purpose hybrid (DP) or semidwarf (SD) corn ( Zea mays L.) variety. In SC systems, full‐season hybrid corn (HC) was planted without preceding forage. Six fertilizer N rates (0–224 kg N ha −1 ) were applied to corn. Averaged across N rates, DP and SD corn yielded less (8.2 and 1.8 Mg DM ha −1, respectively) compared to SC (16.4 Mg DM ha −1 ). Total system DM yield was similar for the DC–DP and SC–HC systems, averaging 16.6 Mg ha −1 . Economic return for the SC system was greater than that for the DC–DP system, and was maximized with 134 to 224 kg N ha −1, while return for the DC–DP system was unaffected by N rate. Due to low corn yield and greater production cost, double cropping spring forage with short‐season corn is not a profitable alternative to SC corn.